Highly effective teachers of vulnerable students practice transcending theory - Poplin, Mary S. 1951-; Bermudez, Claudia 1973- (New York Peter Lang, 2019)
"In these pages lie the quintessential details of highly effective teachers working with students who live in poverty inside our public schools and community colleges. It also contains the words and actions of the teachers that can inspire and direct any current or future teacher who wants to be great and be a part of inspiring young people to fulfill their potential. This is the grist we need to spark a reinvigorated critical national conversation about what it takes to really have highly effective teachers in low-income public schools and whether we have the moral courage to work as hard as they do to make educational equity a reality in our nation"--Provided by publisher.
Enter the world of highly effective teachers / Mary Poplin -- "My classroom is not broken" : interviews with highly effective teachers / Claudia Bermâudez -- "She wants us to be the best and change the world" : how students perceive highly effective teachers / Wendy Moore & Claudia Bermâudez -- "The sky is the limit" : the essential teaching practices of successful teachers of Latino English learners / Wendy Moore -- "She won't give up on you" : math instruction as cultural capital for English learners / David Tarazâon -- "Her method of teaching is extraordinary" : preferred strategies for reclassification of English learners / Kim Hall -- "I always have them in pairs" : the essential practices of teacher talk and structured group work / Calista E. Kelly -- "She kept me in the game" : how black males perceive effective teachers / Matthew Smith -- A culture of honor : highly effective teachers of African American students in grades 4-12 / Jaquet Dumas -- "He keeps me on track and prevents me from lollygagging" : insights from a Native American tutoring program / Alejandro B. Lopez -- "Believe you have something to say" : successful community college teachers of developmental english classes / Rebecca Hatkoff & Claudia Bermâudez -- Challenging class : how highly effective teachers mitigate social class reproduction in working-class communities / Rebecca Hatkoff -- Finding the experts : selection criteria of highly effective teachers / June K. Hilton -- "He never leaves someone behind" : reflections and recommendations for practice, policy, and further study / Mary Poplin & Claudia Bermâudez.
Includes bibliographical references and index.
Keywords: Students with social disabilities -- Education -- United States; Effective teaching -- United States